Legality of Appointment of Village Apparatus according to Article 49 Paragraph (2) of Law Number 6 of 2014 concerning Villages in Ujung Padang Village, Alas Maras Subdistrict, Seluma Regency - Jenzen Idianza; Sandi Aprianto; M. Arafat Hermana (Fakultas Hukum Dehasen, 2022)
The purpose of this study was to determine the procedures for the appointment of old village officials and new village officials in the village of Ujung Padang and to find out the validity of the appointment of old and new village officials in the village of Ujung Padang in terms of Law Number 6 of 2014. The research method in this paper is the method Qualitative research is research that refers to the legal norms contained in legislation and court decisions as well as norms that live and develop in society. Based on the results of an interview with the Ujung Padang Village Head on July 5, 2022, he explained that,